Visual Thinking in an active university teaching-learning methodology - Gutiérrez-Arenas, Mª del Pilar; Corpas-Reina, Carmen; Ramírez-García, Antonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Knowledge Society is characterised by continuous contact with information of a markedly visual nature. It is not strange, therefore, to implement a methodology based on the image, Visual Thinking, in the university classroom. The methodology used is quantitative in nature. We present the results of the application of this tool to 401 students of three degrees of the University of Cordoba, who express a high level of satisfaction with the experience and improvements in the learning of the subjects. Visual Thinking is considered a tool that favours student involvement through the use of images.